The psychological barriers for higher education students’ ability of giving at Salahuddin University - Salwa Ahmed Amin (Zanco Journal of Humanity Sciences)
This study aims to identify the psychological barriers for higher education students’ ability of giving at Salahuddin University. To achieve this aim، the researcher utilizes Shaqeer’s Scale (2002) for psychological barriers (35 items) and Raheem’s scale (2017) for the ability of giving (30 items). The two scales were sent to experts to check face validity، which calculated as (0.87) for the ability of giving scale and (0.82) for the psychological barriers scale. Due to this high level of validity، the two scales were adopted as are without making any change in the items.